2006
DOI: 10.1186/bf03352598
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the 30-year creep trend on the Ismetpaşa segment of the North Anatolian Fault using an old geodetic network

Abstract: The Ismetpaşa segment of the North Anatolian Fault was ruptured during both the 1944 (Mw = 7.2) Gerede and 1951 (Mw = 6.9) Kurşunlu earthquakes. The field studies carried out in the aftermath of these two major earthquakes showed that the Ismetpaşa segment had experienced a creep movement. To monitor the surface creep, a geodetic network with six control points was established on the segment. This network was observed three times-in 1972, 1982 and 1992. Based on our evaluations of those observations, the creep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Therefore, the geodetic network established on the Ismetpasa segment was observed one more time in 2002. Based on this observation campaign, the creep rate of the segment between 1992-2002 was obtained 0.7 cm/year (Kutoglu and Akcin, 2006). This result was also confirmed by the study of Cakir et al (2005), using InSAR technique.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Therefore, the geodetic network established on the Ismetpasa segment was observed one more time in 2002. Based on this observation campaign, the creep rate of the segment between 1992-2002 was obtained 0.7 cm/year (Kutoglu and Akcin, 2006). This result was also confirmed by the study of Cakir et al (2005), using InSAR technique.…”
Section: Introductionsupporting
confidence: 65%
“…This first result was compatible with 2.2 cm/year slip rate of the NAF (McClusky et al, 2000). After the discovery of its creep behavior, the Ismetpasa segment had been the center Correspondence to: H. S. Kutoglu (kutogluh@hotmail.com) of interest; many studies using different surveying techniques were carried out to determine its creep rate in different periods (Ambraseys, 1970;Aytun, 1982;Altay and Sav, 1991;Cakir et al, 2005;Kutoglu and Akcin, 2006). A list of these studies and the creep rates obtained are shown in Fig.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…After Ambraseys, the first geodetic study was started by establishing triangulation and trilateration network across the fault near Ismetpasa. The geodetic measurements indicate that the rate of creep is 9.3±0.7 mm/yr [10] and 7.8±0.5 mm/yr [11]. Using InSAR technique, Cakir et al, [8] estimated the rate 8±3 mm/yr for the creeping on the section.…”
Section: Geoscience Studiesmentioning
confidence: 99%